CAN NOTARY IMPLEMENT ITS AUTHORITY IN MAKING AN AIRCRAFT MORTGAGE DEED? - Preliana, Okta; Y, Annalisa; Trisaka, Agus (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to analyze the regulation of aircraft classification in terms of material law relating to collateral law in Indonesia. In addition, it examines the implementation of the power of the Notary as a public office holder in preparing an Aircraft Mortgage deed which is mandated in the law, but is constrained due to the absence of regulation on aircraft mortgage. Meanwhile in the business world, the aviation industry currently requires capital to develop its business by making credit agreements with banks. The results showed that aircrafts are categorized as registered objects and can be used as collateral. However, the stipulation of registered objects is not regulated in Civil Code which only regulates the classification of immovable objects. Classification of registered objects towards aircraft can be matched with immovable objects as stipulated in Civil Code by using a mortgage guarantee agency. Like the registered objects carried by the Ship (Shipping Law) it uses a mortgage guarantee. This provision can also be applied on aircraft by using analogy mechanisms. To overcome this, the alternative adopted by a notary is to make a fiduciary deed because what guaranteed by aircraft is engines, not a plane as a whole, and it is categorized as a movable object. Alternatively, the notary makes a "Transfer of Guarantee and Power of Attorney Deed" containing a statement of the existence of debt guaranteed by aircraft. In the scenario of default of the borrower, the creditor is given the right and full authority to make the sale and in the deed the name of the guarantee agency is not stated. Thus, an aircraft mortgage regulation becomes urgent to be prepared by the government so that there is no legal vacuum.